2022
DOI: 10.1111/andr.13184
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of remote ischemic postconditioning in rat testes after testicular torsion/detorsion

Abstract: Background: Testicular torsion/detorsion can lead to severe testicular damage.The organ-protective effect of remote ischemic postconditioning (RLIPost) against ischemia/reperfusion injury has been characterized; however, it remains unknown whether RLIPost has a testicular protective effect.Objectives: Here, we tested the hypothesis that RLIPost can protect the testes in a rat model of testicular torsion/detorsion in vivo. Materials and methods:Male Sprague-Dawley rats were assigned to sham-operated, control, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In this study, we investigated the potential protective effects of carvacrol on testicular injury induced by T/D in a rat model. Our findings revealed significant alterations in various parameters, including histopathological changes, oxidative stress markers, and serum testosterone levels, highlighting the potential therapeutic role of carvacrol in mitigating testicular damage (12,13). Histopathological analysis plays a crucial role in assessing tissue damage and pathological changes (14).…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we investigated the potential protective effects of carvacrol on testicular injury induced by T/D in a rat model. Our findings revealed significant alterations in various parameters, including histopathological changes, oxidative stress markers, and serum testosterone levels, highlighting the potential therapeutic role of carvacrol in mitigating testicular damage (12,13). Histopathological analysis plays a crucial role in assessing tissue damage and pathological changes (14).…”
Section: Discussionmentioning
confidence: 64%
“…It is worth mentioning that we previously found that remote ischemic conditioning executed after testicular detorsion (RIPost) protected rat testes against testicular I/R injury. However, ERK1/2 phosphorylation was increased only in RIPost-treated ipsilateral testes but not in contralateral testes after detorsion when compared to rats in the non-RIPost-treated testicular I/R group [ 12 ]. Taken together, our results indicate that RIPC and RIPost may protect ipsilateral testis against testicular I/R via activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsion and detorsion were performed under anesthesia with sodium pentobarbital (50 mg/kg, i.p.) [ 11 , 12 ]. Testicular torsion/detorsion surgerical procedure was performed based on previously publications [ 6 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition of the contralateral untwisted testis is debatable after unilateral testicular ischemia-reperfusion. In some studies, it has been reported that unilateral testicular ischemia-reperfusion induces harmful effect on the contralateral testis [ 51 , 52 ]. In contrast, other studies have indicated that no injury is observed in the contralateral testis [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%